Detection of immunoglobulins containing plasma cells in the thymus, bursa of Fabricius and spleen of vaccinated broiler chickens with Newcastle disease virus vaccine - Md. Abdul Masum; Md.Zahirul Islam Khan; Morsheda Nasrin; M. Nazmul Hassan Siddiqi; Mohammed Zubayer Ibna Khan; Md. Nabiul Islam (Elsevier, 2014)
Mobilization of immunoglobulins (Igs)-containing plasma cells (IgA, IgG and IgM) in the spleen, bursa of Fabricius and thymus was investigated in broiler chickens that were vaccinated with Newcastle disease virus (NDV) vaccine. In the thymus, the Igs-containing plasma cells were distributed in the cortex and medulla. Their frequency and distribution were higher at D14 and at D28. The number of IgG- and IgM-positive cells was greater than IgA-positive cells in thymus. In the bursa of Fabricius, Igs-containing plasma cells were distributed beneath the capsules; within and around the bursal follicles. Their frequency of occurrence signiﬁcantly peaked at D14 and at D28 in comparison to day-old chickens, and IgG-positive cells were signiﬁcantly greater than the IgA- and IgM-positive cells in the bursa of vaccinated chickens. In the spleen, Igs-containing plasma cells were distributed in the white pulp, around the trabeculae, and in the periarterial lymphatic sheath. In this secondary lymphatic tissue, IgG- and IgM-positive cell numbers signiﬁcantly greater